Conception of the Information Society: in the Grip of the Old Wineskins - Šaulauskas, Marius Povilas (Problemos, 2003)
The article deals with fundamental methodological and axiological characteristics of the information society’s concept. It argues, first, that the most widespread understanding of the information society dwells on the existential presupposition, which sensu stricto implausibly posits information society, tentatively endowed with an utmost societal importance, as an already real phenomenon in status nascendi. Second, that such an existential-axiological assumption is articulated along the lines of modern ideological discourse, i.e., in terms of mainstream liberal-socialdemocratic controversies. An article also puts under critical comparative scrutiny the usage of information society’s concept in the public sphere of nowadays Lithuania.